Kesadaran Masyarakat Pesisir Terhadap Degradasi Lahan: Studi Kasus di Pesisir Kota Semarang - Rifandi, Raditya Ahmad; Putra, Rizal Ichsan Syah (Jounal of Enviromental Science Sustainable, 2024)
Semarang City, located on the northern coast of Java Island, faces significant environmental issues including land degradation and tidal flooding, which threaten soil quality and infrastructure. Land degradation, driven by land conversion and unsustainable agricultural practices, along with tidal flooding caused by climate change and land subsidence, has notable adverse effects on coastal communities. This study aims to explore the level of awareness among Semarang's coastal residents regarding these issues, employing survey and in-depth interview methods with 200 respondents from coastal areas. The findings reveal that awareness of land degradation and tidal flooding is moderate, with 60% of respondents showing an intermediate level of awareness and 25% acknowledging the impacts of each issue. Meanwhile, 15% of respondents were less aware and did not have sufficient information about the issue of land degradation. This research underscores the need for enhanced educational and outreach efforts to increase community awareness and participation in environmental mitigation. Improving awareness will aid in developing more effective mitigation strategies to address the environmental challenges faced by Semarang City.